2006
DOI: 10.1002/app.24475
|View full text |Cite
|
Sign up to set email alerts
|

Properties of ligno‐cellulosic bilayered vegetable fabric from ridge gourd

Abstract: ABSTRACT:The two layers of bilayered vegetable fabric from ridge gourd were analyzed by FTIR, chemical, X-ray, and thermogravimetric methods before and after alkali treatment. The morphology of the fabrics in the two layers, before and after alkali treatment, was also studied using SEM technique. The FTIR and chemical analyses indicated lowering of lignin and hemicellulose content by alkali treatment in the fabric of both layers. Further, the X-ray diffraction revealed increase in crystallinity of the fabric b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Overall, however, the compressive strength is found to be higher when alkali treated ridge gourd fabric was used. This is as expected, since alkali treated fabric becomes more crystalline by the removal of a considerable amount of amorphous hemi-cellulose and lignin [10]. In order to improve the compressive properties of these composites, an attempt was made by the authors to hybridize them with glass mat.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Overall, however, the compressive strength is found to be higher when alkali treated ridge gourd fabric was used. This is as expected, since alkali treated fabric becomes more crystalline by the removal of a considerable amount of amorphous hemi-cellulose and lignin [10]. In order to improve the compressive properties of these composites, an attempt was made by the authors to hybridize them with glass mat.…”
Section: Resultsmentioning
confidence: 84%
“…Further, with the use of coupling agents, matrix skin formation is observed on the fiber surface, indicating strong bonding between the fibers and the matrix (Figures 5e and 5f). Varada Rajulu et al [10] has already showed that with alkali treatment, the surface of the fibers in ridge gourd fabric became rough. This may be the reason for better interfacial bonding on alkali treatment.…”
Section: Resultsmentioning
confidence: 97%
“…Similar observation was made in the case of some ligno-cellulosic fibers. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] Overall morphology of the fabric could be favorable for making green composites with fabric reinforcement.…”
Section: X-ray Diffraction Studiesmentioning
confidence: 99%
“…In this direction, some ligno‐cellulosic fibers have been studied by several researchers recently 10. Characteristic studies of various ligno‐cellulosic fabrics have been reviewed for this investigation 11, 12. To identify new natural fibers and fabrics as reinforcement, their properties have to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…10 Characteristic studies of various ligno-cellulosic fabrics have been reviewed for this investigation. 11,12 To identify new natural fibers and fabrics as reinforcement, their properties have to be studied. In this work, the authors have studied the properties of the ligno-cellulosic fabric from Prosopis chilensis (PC).…”
Section: Introductionmentioning
confidence: 99%